DIFFERENTIZED LEARNING WORKSHOP IN AN INDEPENDENT CURRICULUM: PHENOMENON AND SOLUTIONS IN MAPPING STUDENTS' LEARNING NEEDS - Dina Ramadhanti (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
ABSTRACTDifferentiated learning is still a new phenomenon for Indonesian language teachers who are members of the MGMP SMP/MTS Bahasa Indonesia Gugus II Kabupaten Sijunjung. Differentiated learning is still not used massively and not all classes use the Independent Curriculum. Teachers experience obstacles in implementing differentiated learning because the Independent Curriculum is still not used for every level of education. After providing the program material, a question and answer session was held with the teacher and it was discovered several challenges faced by teachers in implementing the Independent Curriculum, namely: teachers must know the various characteristics of students, teachers must prepare diagnostic and formative assessments at the beginning of learning, and teachers must use various sources. One effort that can be made to map students' learning needs is to use a reflective journal. Reflective journals have been widely used for reflection and self-expression for various needs, thinking, and improving learning. The main strengths of reflective journal writing are introspection and reflection. This reflection is carried out by answering several guiding questions. These guiding questions are useful for helping students remember what they have done, the obstacles they have faced, and the efforts they have made to overcome anything that hinders their learning progress.Keywords: Differentiated learning, learning needs mapping, reflective journal  ABSTRAKPembelajaran berdiferensiasi masih menjadi fenomena baru bagi guru-guru Bahasa Indonesia yang tergabung dalam MGMP Bahasa Indonesia SMP/MTS Gugus II Kabupaten Sijunjung. Pembelajaran berdiferensiasi masih belum digunakan secara massif dan belum semua kelas menggunakan Kurikulum Merdeka. Guru mengalami kendala dalam mengimplementasikan pembelajaran berdiferensiasi karena Kurikulum Merdeka masih belum digunakan untuk setiap jenjang pendidikan. Setelah pemberian materi program, dilakukan tanya jawab dengan guru dan diketahui beberapa tantangan yang dihadapi oleh guru dalam mengimplementasikan Kurikulum Merdeka, yaitu: guru harus mengetahui berbagai karakteristik peserta didik, guru harus menyusun asesmen diagnostik dan formatif di awal pembelajaran, dan guru harus menggunakan berbagai sumber. Untuk memetakan kebutuhan belajar peserta didik, salah satu upaya yang dapat dilakukan adalah dengan menggunakan jurnal reflektif. Jurnal reflektif telah banyak digunakan sebagai sarana refleksi dan ekspresi diri dalam berbagai kebutuhan, berpikir, dan peningkatan pembelajaran. Kekuatan utama dari penulisan jurnal reflektif adalan introspeksi dan refleksi. Refleksi ini dilakukan dengan menjawab beberapa pertanyaan pemandu. Pertanyaan-pertanyaan pemandu ini berguna untuk membantu peserta didik mengingat kembali apa yang sudah dilakukan, kendala-kendala yang mereka hadapi, dan upaya yang mereka lakukan untuk mengatasi segala hal yang menghambat perkembangan belajar mereka.Kata kunci: Pembelajaran berdiferensiasi, pemetaan kebutuhan belajar, jurnal reflektif